Decolonisation and nation-building in New Caledonia: Reflections on the 2014 elections. (June 2015) - Chappell, David
The French Pacific island 'collectivity' of New Caledonia has faced serious challenges in decolonising since the Second World War because, unlike Australia, New Zealand, Canada and the US, it is a settler country manqué. Instead of becoming a small minority, the indigenous Melanesian inhabitants (today called Kanak (invariable spelling)) comprise nearly half the population and hold 46% of the seats in the Congress. Most of them seek independence, whereas most settlers want to remain part of France, albeit with autonomy. For a century after French annexation in 1853, colonial segregation onto small, marginal native reserves and a lack of civil rights created a unified consciousness among the 30 indigenous language groups. Apart from forced or low-wage labour situations or conversion by missionaries, they intermingled very little with settlers, who included French convicts and small farmers, ranchers and nickel miners, as well as indentured Asian labourers and Polynesian workers from Wallis and Futuna or French Polynesia. The Kanak finally received civil rights in 1946 and were a demographic majority, so they supported a multiracial political party for a generation while the territory gained autonomy. However, in the 1960s, Paris revoked such self-governing powers during a nickel boom, and new immigration made the Kanak a minority, which hardened ethno-political polarisation and sparked an independence movement that culminated in a Kanak revolt in the 1980s. Two peace accords ensued, which restored autonomy and proposed a 'common destiny' for local citizens. The May 2014 elections chose a Congress that can hold a referendum on independence, but factionalism within each ethno-political bloc delayed forming a cabinet until April 2015, when some pro-independence leaders chose to cooperate with some loyalists.